32nd International Symposium on Microscale Separations and Bioanalysis (MSB 2016). (September 2016) - Ramautar, Rawi
32nd International Symposium on Microscale Separations and Bioanalysis, Niagara-on-the-Lake, Canada, 3–7 April 2016 The 32nd edition of the International Symposium on Microscale Separations and Bioanalysis (MSB) was held in Niagara-on-the-Lake, Canada, from 3 to 7 April 2016. This article outlines the aim and the main distinctive features of the MSB symposium. A selection of the scientific research presented at MSB 2016 is highlighted with a special focus on microscale separation developments in the fields of sample preparation, (glyco)proteomics and metabolomics.